Pembentukan Karakter Siswa Melalui Kegiatan Kepramukaan Di MI Taufiqiyah Semarang - Khoriyatul Muna; Najma kamila Fitri (Universitas Negeri Makassar, 2023)
Abstract. This article discusses the formation of students' character through scouting activities at MI Taufiqiyah Semarang. This research aims to determine how scouting activities are carried out at MI Taufiqiyah Semarang and how the values of character education are instilled through scouting extracurricular activities in daily life. The method used is a qualitative descriptive method to describe the situation of scouting activities at MI Taufiqiyah Semarang. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The implementation of scouting extracurricular activities at MI Taufiqiyah Semarang has been carried out well and structured. Scouting extracurricular activities at MI Taufiqiyah Semarang are conducted every Saturday, starting at 07:30, and are mandatory extracurricular activities for students in grades 3, 4, and 5. The objectives of conducting scouting activities at MI Taufiqiyah Semarang are to shape character, personality, and noble morality of young people, instill a spirit of nationalism, love for the homeland, and defend the nation, and improve skills so that they are ready to become useful members of society, patriotic and resilient fighters, and competent future leaders of the nationKeywords: Extracurricular, Scouting, Character